(untitled) - Arsa, Cliford Polo (Can Tho, 2020)
Two consecutive experiments were conducted to determine the suitable seaweed species as shelter and stocking density in nursing of mud crab Scylla paramamosain crablets in indoor condition. In the first experiment, evaluation of different densities of seaweed species as a shelter on survival and growth rate of crablets comprised seven treatments. The control treatment featured no shelter (i.e. without seaweed in the culture tank) and in the other six treatments, red seaweed (Gracilaria tenuistipitata) or green seaweed (Enteromorpha intestinalis) were supplied to the rearing tanks as shelter at different density levels of 0.5, 1 and 2 kg/m². Triplicate groups of instar 2 crablets were stocked at a rate of 300 ind./m² for four weeks.
Keywords: Nuôi cua,Crab culture